2017
DOI: 10.14569/ijacsa.2017.080430
|View full text |Cite
|
Sign up to set email alerts
|

A RDWT and Block-SVD based Dual Watermarking Scheme for Digital Images

Abstract: Abstract-In the modern era, digital image watermarking is a successful method to protect the multimedia digital data for example copyright protection, content verification, rightful ownership identification, tamper detection etc. In this paper for improving the robustness and security, a Dual watermarking approach using Redundant Discrete Wavelet Transform (RDWT), block based singular value decomposition (SVD) and Arnold transform is presented. There are two gray scale watermarks, one is Prime watermark and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…It is found that NC 1 and NC 2 of proposed scheme are much higher than the values obtained in [30] for same set of attacks. Table 6 emphasizes the efficacy of proposed algorithm by comparing it with other reported techniques such as [19] a , [19] b , [21] and [22] where [19] a signifies technique without BPNN and [19] b denotes technique using BPNN. Symbol '*' means NC values were not reported for these attacks.…”
Section: Simulation Results and Its Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that NC 1 and NC 2 of proposed scheme are much higher than the values obtained in [30] for same set of attacks. Table 6 emphasizes the efficacy of proposed algorithm by comparing it with other reported techniques such as [19] a , [19] b , [21] and [22] where [19] a signifies technique without BPNN and [19] b denotes technique using BPNN. Symbol '*' means NC values were not reported for these attacks.…”
Section: Simulation Results and Its Analysismentioning
confidence: 99%
“…However, this method does not yield sufficient value of correlation coefficient. Another similar method is investigated in [22]. Major difference lying in both schemes is use of image transforms.…”
Section: Introductionmentioning
confidence: 99%
“…In RDWT the size of the sub band at the same decomposition level is the same as the host image but decreased in DWT. RDWT analysis and synthesis equations can be expressed as the following equations [7,10]: where * means convolution, ↑2 means up sampling and ↓2 means down sampling at each iteration in DWT. Down sampling decreased the size of each sub band and increased the decomposition level.…”
Section: Redundant Discrete Wavelet Transformmentioning
confidence: 99%
“…This is due to the fact that bigger singular values do not only ensure the most energy of an image, but also withstand attacks. For that reason, the matrix S has been used as a choice for embedding a robust watermark [7].…”
Section: Singular Value Decompositionmentioning
confidence: 99%
“…This process allows dual watermarks to be embedded many times in the host image which increases the robustness against several attacks. A dual watermarking approach using Redundant Discrete Wavelet Transform (RDWT), block based singular value decomposition (SVD) and Arnold transforms [2] is presented. This scheme has the high embedding capacity and a little degradation in the image.…”
Section: Related Workmentioning
confidence: 99%